2000
DOI: 10.1119/1.19407
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and mechanisms of Thomson’s jumping ring

Abstract: Measurements of the phase delay of the current and force on a ring floated on a commonly available Thomson's jumping ring apparatus were performed for phase angles from 12°to 88°. The force and phase data show excellent agreement with a linear inductive model. We find that the demonstration, as usually performed with large highly conducting rings, operates in the inductance-dominated regime at 60-Hz line frequency. Stroboscopic photographs of the jumping ring, for both room-temperature and 78-K rings, confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Tjossem and Cornejo reported phase shifts for a range of frequencies with 60 o at 60 Hz. 10 Both of these estimates are consistent with our results.…”
Section: Measuring the Phase Shiftsupporting
confidence: 92%
See 2 more Smart Citations
“…Tjossem and Cornejo reported phase shifts for a range of frequencies with 60 o at 60 Hz. 10 Both of these estimates are consistent with our results.…”
Section: Measuring the Phase Shiftsupporting
confidence: 92%
“…9 Tjossem and Cornejo also reported the force on the ring is greater at the bottom and decreases toward the top. 10 In addition, the latter authors found that the ring takes several cycles, or 0.10 s, to clear the core, using strobe Table I. Results of a kinematics experiment for an aluminum ring 2-cm high, 6 cm in diameter, and 3-mm thick, giving the final velocity leaving the core, the time to jump, number of quarter-cycles (t/0.00417 s), and the average acceleration relative to the acceleration of gravity, g. See Fig.…”
Section: Why the First-quadrant Explanation Failsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic braking has also found a number of important applications in the present technology [9]. Both the jumping ring [4,6] and the vertical motion of a small magnet inside a conductive tube are manifestations of Faraday magnetic induction and have recently begun to be studied thoroughly in the laboratory [1][2][3] because of their pedagogical value. It offers, for instance, a good opportunity for a very low cost, honours degree or senior undergraduate experiment on Faraday induction, and it is also an excellent case for illustrating the modelling of an intriguing physics phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting MagLev systems is the "Thomson's Jumping Ring" [1], [24], which was created by Elihu Thomson (1853Thomson ( -1937 and consists of an induction coil with a core of some ferromagnetic material and a ring placed in the core (see Figure 1 for a detailed diagram). When an alternating current circulates in the coil, it is induced a current in the ring, the magnetic field due to this induced current opposes the field induced by the coil producing a total repulsive force on the two windings and, in this way, making the ring rises above the core of the coil.…”
Section: Introductionmentioning
confidence: 99%